Exploring the cardiovascular effects of hypertonic lactate: a systematic review of animal studies - Oskar Kjærgaard Hørsdal (Open Exploration Publishing Inc., 2024)
Background: The naturally occurring metabolite lactate has traditionally been considered as a waste product of anaerobic metabolism whose production was confined to hypoxic states. However, more evidence supports that lactate is a preferred oxidative substrate for the myocardium when present in high plasma levels. Small-scale clinical studies have found that infusion of exogenous hypertonic sodium lactate (HSL) increases cardiac output and stabilizes the haemodynamic profile. More comprehensive studies investigating haemodynamic or cardiovascular effects of HSL have been conducted using different animal models of disease. Methods: We performed a broad systematic search of electronic databases PubMed and Embase to identify animal studies in which haemodynamic or cardiovascular effects of HSL were reported. A total of 135 studies were identified. Nineteen studies were included in this review. Different disease models were included including sepsis (n = 4 studies), cardiac arrest (n = 3 studies), myocardial infarction (n = 2 studies), haemorrhagic shock (n = 3 studies) while studies on healthy hearts (n = 4 studies) were included. Also, three studies investigating the cardioprotective and cardiometabolic roles of HSL were included. Results: The review explains several beneficial haemodynamic effects of HSL infusion during a variety of disease states including increased cardiac output, increased microcirculation, and decreased systemic inflammation. Only a few studies identified the negative effects of HSL infusion. This paper suggests that high doses of lactate serve as an important cardiac fuel during crises and can also function as a pH buffer. However, the review revealed significant flaws in the reporting quality of the majority of studies. Discussion: HSL infusion holds promise as a potential treatment fluid for a variety of diseases. Future translational studies should focus on enhancing reproducibility, study design, and study reporting.